Kinetic analysis of ethanol and dimethyl ether flames with hydrogen addition. (9th February 2017) - Luo, Minye; Liu, Dong
Abstract: The influences of hydrogen addition on laminar premixed ethanol/O2 /Ar and DME (dimethyl ether)/O2 /Ar flames under fuel-lean ( Ф = 0.8) and fuel-rich ( Ф = 1.7) conditions at 1.0 atm are studied by the detailed kinetic analysis. The comparisons are conducted to illustrate the characteristics of these two isomers affected by H2 addition. The chemical effects of H2 addition on ethanol and dimethyl ether flames are distinguished and separated from its dilution and thermal effects respectively. The results show that the mole fractions of CH4, C2 H6 and CH2 O in DME flames are larger than those in ethanol flames. The influences of hydrogen addition on CH4, C2 H6 and CH2 O in ethanol flames are weakly. The chemical effects of H2 addition promote the production of CH4, C2 H6 and CH2 O and shift the profiles to the upstream side in DME flames. The dilution and thermal effects which decrease the mole fractions of these species and shift profiles to the downstream side are more dominant for DME flames. Meanwhile, the mole fractions of C2 H2, C2 H4 and CH3 CHO in DME flames are less than those in ethanol flames. The H2 chemical effects which mainly promote the formation of C2 H2 and C2 H4 in ethanol flames suppress the production of these species in DME flames slightly for the fuel-rich condition. The dilution and thermal effects of hydrogen on these species are more dominant in ethanol flames than those in DME flames. Highlights: H2 chemical effects on DME and ethanol flames are comparatively studied. Chemical effects of H2 addition are isolated from thermal and dilution effects. H2 chemical effects promote the production of CH4, C2 H6 and CH2 O in DME flames. H2 chemical effects suppress formations of C2 H2 and C2 H4 in DME fuel-rich flames. C2 H2, C2 H4 and CH3 CHO concentrations in ethanol flames reduce with H2 addition.